A study of weekly paclitaxel vs weekly cisplatin with concomitant chemoradiation in locally advanced head and neck cancer - Daru, Himadri Kumar; Sobita Devi, Yumkhaibam; Sobita Devi, Yumkhaibam; Singh, Jaichand; Singh, Jaichand (International Journal of Research in Medical Sciences, 2017)
Background: The purpose of this study was to compare the role of concomitant chemoradiation using paclitaxel versus cisplatin in locally advanced head and neck cancers. Methods: 52 patients were randomly assigned to one of the two concomitant chemoradiation arms: arm I (n=26) and arm II (n= 26) who received injection of paclitaxel 40 mg/m2 I/V 1-hour infusion before radiation, repeated weekly for 6 cycles, and cisplatin 30 mg/m2 I/V 1-hour infusion before radiation, repeated weekly for 6 cycles, respectively. The planned radiotherapy dose was 66-70 Gy, 2 Gy/day, 5#/Week in 6-7 weeks. Results: Response rates were 69.2% and 57.7% in arm I and arm II, respectively. There was no statistically significant difference observed between the study group and the control group (P = 0.85) On median follow up of 7-15 months, Disease free survival was (83.3%) in arm I compared with (73.3%) in arm II but the difference was statistically insignificant. Local toxicities including mucositis, dysphasia and skin reactions were more in the study the haematological toxicity was generally mild. On the contrary, non-hematologic toxicities were severe. Grade IV mucositis occurred in 26.9% in arm I and in 3.8% in arm II (P = 0.003). Moreover, grade IV dermatitis were encountered in 23.1% in arm I (P = 0.00). Conclusions: Both concomitant chemoradiotherapy regimens were easily given in the outpatient clinic. The regimen based on paclitaxel was more effective; however, the difference was insignificant.